Standardized Whole-Blood Immunophenotyping Panels on Flow Cytometry for Transplant Recipients and Clinical Trials. (July 2018) - Vera, Elvira Jimenez; Chew, Yi Vee; Burns, Heather; Anderson, Patricia; Williams, Lindy; Dervish, Suat; Wang, Xin Maggie; Yi, Shounan; Hawthorne, Wayne; Alexander, Stephen; O'Connell, Philip; Hu, Min
Abstract : Introduction: Immunophenotyping of whole blood by flow cytometry is a reliable, fast, and easy method used to obtain a large amount of information on the effects and outcomes of different treatments in transplantation on immune phenotype with minimal impact on the patient. Aim: 1) To establish whole-blood immunophenotyping panels for transplant recipients, 2) To develop a concise method involving the standardisation of reagents, sample handling, instrument setup and data analysis. Methods: Absolute cell count (TruCount) and seven leukocyte-profiling panels containing 8-10 marker-antigens (46 of which were unique within the panels) consisting of subsets and/or status of granulocytes, monocytes, DCs, B, NK, , and T cells including Tregs and NKT were used to monitor the immune profiles of paediatric kidney transplant and adult islet cell transplant recipients. Whole-blood samples were stained and acquired on a BD-LSRFortessa and Flowjo was used for data analysis. BD™ Cytometer Setup and Tracking beads monitored cytometer performance. Sample staining was performed within 2 hours of blood sample collection. The accuracy and variability of these panels were determined and 100-300 μ l whole-blood was used for each panel. Results: The 46 antibodies were titrated and the staining index (SI) was calculated (CD45BUV395 in Fig.1A) for panel optimisation. Application settings on a BD LSRFortessa, measurement of the spillover spreading matrix (SSM) for each panel [SSM in Panel 3 (Tab.1)], and optimal antibody quantity for the panel-cocktail were established. Auto-analysis templates and gating strategies (Panel 1 in Fig.1B) to target subsets of immune-cells were set up and blood sample collection, preparation, antibody cocktails, and staining protocols were standardised. 9 paediatric kidney transplant patients, 4 islet transplant patients (which are to be followed until two years post third islet transplant), 13 T1D patients and 8 control samples have been evaluated to date. The ability to identify consistent immune subsets across all panels over 6 months (Fig.1C from TruCount Panel) was achieved, and was used to longitudinally track the proportions of cell populations in transplant patients (Fig.1D Panel 1). Conclusion: We standardised immune panels and procedures for absolute cell numbers and multiple subsets of immune cells for monitoring a range of individuals including healthy controls, paediatric kidney recipients, T1D, and islet transplant recipients. We have demonstrated that immunophenotyping by flow cytometry is a reliable, consistent, and fast technique that allows the detection of changes in absolute cell numbers of leukocyte subsets from any recipients' whole blood. This immunophenotyping by flow cytometry is a non-invasive technique which requires less than 1.5ml of whole blood and may be a useful tool for monitoring changes in the immune profile of individuals in a range of clinical trials. Birgit Sawitzki. Mathias Streitz. Figure. No caption available.